Food irradiation research and technology (Blackwell Pub., 2006)
Food Irradiation Research and Technology appeals to a broad readership: industry food scientists involved in the processing of meat and fish, fruits and vegetables; food microbiologists and radiation processing specialists; government and industry representatives involved in the import and export of food commodities; and industry, local, and state officials involved in educational efforts regarding food irradiation